DENDRIMERS IN ANTICANCER TARGETED DRUG DELIVERY: ACCOMPLISHMENTS, CHALLENGES AND DIRECTIONS FOR FUTURE - A. M. Amjad (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
Dendrimers are nanoparticles with unique features including globular 3D shape and nanometer size. The availability of numerous terminal functional groups and modifiable surface engineering permit modification of dendrimer surface with several therapeutic agents, diagnostic moieties and targeting substances.The aim. To enlighten the readers regarding design, development, limitations, challenges and future directions regarding anticancer bio-dendrimers.Materials and methods. The data base was represented by such systems as Medline, Cochrane Central Register of Controlled Trials, Scopus, Web of Science Core Collection, PubMed. gov, Google-Academy. A search was carried out for the following keywords and combinations: Polypropylene imine (PPI); Poly-L-lysine (PLL); polyamidoamine (PAMAM); cancer; drug delivery; dendrimers.Results. High encapsulation of drug and effective passive targeting are also among their therapeutic uses. Herein, we have described latest developments in chemotherapeutic delivery of drugs by dendrimers. For the most part, the potential and efficacy of dendrimers are anticipated to have considerable progressive effect on drug targeting and delivery.Conclusion. The newest discoveries have shown that the dendritic nanocarriers have many unique features that endorse more research and development.